Forecasting and Responsible Innovation: A Book Review - Moniz, António Brandão (Frontiers in Sociology, 2022)
The new book edited by Rodríguez and colleagues focuses on the topic of forecasting and responsible innovation. The original title is “Anticipación e Innovación Responsible: La construcción de futuros alternativos para la ciencia y la tecnologia” (Forecasting and Responsible Innovation: The construction of alternative futures for science and technology), and was published by Biblioteca Nueva, Madrid. Throughout this text, the reviewer is using the term forecasting instead of anticipation to convey the Spanish concept of “anticipación.” Both concepts are usually applied to “the act of looking forward” (Merriam-Webster dictionary1) or “the act of expecting or foreseeing something; expectation or presentiment” (Farlex free dictionary2) The concept of forecasting is usually used in scientific debate to mean “to estimate or predict in advance” (American Heritage Dictionary of the English Language, 2016) or “the process of making predictions based on past and present data and most commonly by analysis of trends” (Wikipedia3) (Glenn, 1994, p. 4) expressed this definition well by saying that “studying the future is not simply economic projections or sociological analysis or technological forecasting, but a multi-disciplinary examination of change in all major areas of life to find the interacting dynamics that are creating the next age.” The concept has been developed mainly by Armstrong (2001) and followed by Farrukh and Holgado (2020), Schnaars (2009), and Marinakis (2012), among others. The editors are professors and researchers from the University of Basque Country (EHU) and from the University of Mondragon (MU). The book involves a whole set of experts on the topic, including the editors themselves (Hannot Rodríguez, Sergio Urueña, Andoni Eizagirre, and Oier Imaz), and Armin Grunwald, René von Schomberg, Javier Garcia Fronti, Domingo García Marzá, Andoni Ibarra, and others. Although still published just in Spanish, it is an important contribution to the social sciences and philosophy of sciences regarding the analysis of alternative sociotechnical futures with strong ethical principles, which delineates an innovative approach in an era when the formation of public opinion largely suffers from systematic distortions based on vested interests.